Using digital word sorts as an extension of regular word sorts to impact spelling performance and attitude scores of 4th grade students with learning disabilities - Jo Shoemaker (My University, 2015)
The purpose of this single-subject design action research study was to determine how the use of digital word sorts as an extension to regular word study might impact the spelling performance and attitude of two 4th grade students with disabilities. The spelling test averages and attitude surveys scores were analyzed for an increase or decrease in performance of the participants who acted as their own control. An increase in correctly spelled words indicated a positive impact although the attitude survey provided insufficient data for determining change in attitude.
Going Digital with Word Sorts
Keywords: Digital word sorts; Spelling strategies; Spelling instruction; Attitudes